The readiness of industry for a transformative recovery from COVID 19. (21st December 2020) - Fankhauser, Sam; Kotsch, Raphaela; Srivastav, Sugandha
Non-technical summary: Many countries are committed to emerge from COVID 19 on a more sustainable environmental footing. Here we explore what such a structurally transformative recovery would mean for the manufacturing sector of 14 major economies. We find that all countries have zero-carbon growth opportunities post-COVID and comparative advantages in some sectors, but industrialised countries and the East Asian economies, especially South Korea, appear best positioned, thanks a push in low-carbon innovation that predates the pandemic. Technical summary: We construct two indicators to assess the readiness of manufacturing in 14 countries to move toward zero-carbon products and processes post-COVID 19. The first indicator is the extent to which country-sectors have already started to convert to zero-carbon products and processes. This is measured by the relative low-carbon innovation in different country sectors (using global patent data). The second indicator is the ability of country-sectors to gain and maintain market share. This is measured by existing comparative advantages, using the Balassa index of revealed comparative advantage. Taken together the two indicators paint an intuitive picture of the strengths, weaknesses, opportunities and threats (SWOT) faced by different sectors, which can guide countries in their recovery strategies. Social media summary: A zero-carbon recovery from COVID must be led by industry. It requires clean innovation based on comparative advantage.